India's skills challenge : reforming vocational education and training to harness the demographic dividend - Mehrotra, Santosh [Herausgeber] (Oxford University Press, 2014)
"Although India is one of the largest economies in the world, its skill challenges are huge. Despite the tremendous growth and diversification, over half of India's population lacks primary education. Only a fraction of people possess any formal or vocational education and training (VET). India's 12th Planning Commission targets creating around 100 million jobs by 2025 which means millions of people would need VET in addition to primary education. In order to encourage the growth of VET in both public and private sectors, vocational training must expand in schools and higher education institutions. Another critical factor which would help expand VET is industry participation. Apprenticeships and training system must be encouraged from within and the national vocational or skills qualification framework with new occupational standards and competency based curriculum must be implemented. Based on primary surveys of vocational training providers and enterprises, this book is a first to provide a comprehensive agenda of reforms to improve the employability of India's youth. Without the rapid and effective implementation of this reform agenda, India may not be able to harness its demographic dividend which is predicted to last only for another quarter of a century." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; P 3.2.1 Ausbilder; I 2.3.4 Asien; Bildungssystem; Berufsbildungspolitik; Demografischer Wandel; Berufsbildung; Berufsausbildung; Qualifikationsentwicklung; Indien